Profitability Behavior of Plastic Industries in Indonesia - Pardosi, Erwin Mangaratua; Mulyana, Bambang (The Economics and Finance Letters, 2019)
This study aims to analyze the effects on the profitability (net profit margin, return on assets and return on equity) of plastic companies by internal influences (current ratio, debt to equity ratio and total asset turnover) and external influences (exchange rate, petroleum price and inflation). The object of the research is the plastic industries registered in the Indonesian stock exchange with a total of 9 industries and in the period 2012 - 2017. The methodology used is descriptive quantitative research and causality with purposive sampling technique and panel data regression analysis. The results of this study indicate that the current ratio has a partially positive effect, particularly significant in terms of net profit margin. Current ratio and total asset turnover also have a partially positive effect, with significant return on assets. Debt to equity ratio partially has a partially negative effect, but a significant return on equity.